Behavioural responses to improved information supply and demand management in transport: A methodological approach illustrated by a case study in Barcelona - van ZANTEN, Nathalie; NUKAMP, Peter; PEPPING, Gerard (European Spatial Research and Policy, 1994)
This paper has two aims: ( 1) it offers an analytical framework for transport telematics policy with a particular view on behavioural responses of road users, and (2) it illustrates the methodology developed by means of a simple case study. The use of a so-called nested approach appears to offer a promising cohesive framework, which is tested by means of an empirical investigation into the impacts of information-based traffic control measures during the Olympic Games in Barcelona.